Religion and Politics in Latin America : the Catholic Church in Venezuela & Colombia. - Levine, Daniel H. (Princeton : Princeton University Press, 2014)
This book explores the transformations in religion in conjunction with political change. Professor Levine suggests, highlights the dynamic and dialectical interaction between religion and politics in general, and addresses the more universal problem of relating thought to action Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books w.
Print version record.
Cover; Contents.
Master record variable field(s) change: 610
Keywords: Catholic Church; Catholic Church; Catholic Church; Christianity and politics -- Catholic Church; Venezuela -- Politics and government -- 1830-; Colombia -- Politics and government -- 1946-1974.; Colombia -- Church history -- 20th century; RELIGION -- Christianity -- Catholic; Christianity and politics -- Catholic Church; Politics and government; Colombia; Venezuela; Since 1830; Electronic books; Church history